Peran Guru Sekolah Minggu dalam Menanamkan Nilai-nilai Moderasi Beragama pada Anak - Supit, Sugiyanti; Thomas, Art; Loupatty, Vera (Jurnal Ilmiah Religiosity Entity Humanity (JIREH), 2024)
It is very important to teach religious moderation to children from an early age, in this case Sunday school at the Paul Congregation TWM Manado, as one of the congregations located in the center of the city of Manado. Religious moderation leads to an attitude of life that is open, friendly, tolerant, and not extreme in building relationships with fellow human beings of different religions. In this regard, Sunday school teachers play an important role in guiding and teaching children about religious moderation. This study aims to find out the understanding of Sunday school teachers at the Paul Congregation TWM Manado regarding religious moderation. The research method used is qualitative by using literature studies and interviews. The results of the study show that Sunday school teachers' understanding of religious moderation still needs to be developed because according to all informants, religious moderation is not familiar for them. Therefore, training on religious moderation is an urgent need for Sunday school teachers at the Paul Congregation TWM Manado.